The Cosserat brothers and generalized continuum mechanics - Erofeev, Vladimir Ivanovich (Computational Continuum Mechanics, 2009)
This paper presents an overview of the major milestones in the life and research activity of Eugene and Francois Cosserat - the founders of generalized continuum mechanics. The current status and future prospects of generalized continuum mechanics are discussed.